2001
DOI: 10.1016/s1097-2765(01)00386-0
|View full text |Cite
|
Sign up to set email alerts
|

TIP41 Interacts with TAP42 and Negatively Regulates the TOR Signaling Pathway

Abstract: In Saccharomyces cerevisiae, the rapamycin-sensitive TOR kinases negatively regulate the type 2A-related phosphatase SIT4 by promoting the association of this phosphatase with the inhibitor TAP42. Here, we describe TIP41, a conserved TAP42-interacting protein involved in the regulation of SIT4. Deletion of the TIP41 gene confers rapamycin resistance, suppresses a tap42 mutation, and prevents dissociation of SIT4 from TAP42. Furthermore, a TIP41 deletion prevents SIT4-dependent events such as dephosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
236
9
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(277 citation statements)
references
References 28 publications
10
236
9
9
Order By: Relevance
“…Thus, as with PP4C, PP4R2 appeared to be present in a complex with PP4R3␣ and/or PP4R3␤. In addition to these proteins, the PP4R2 pull-down also yielded MGC3794, the human homolog of S. cerevisiae Tip41 (Tap42-interacting protein, molecular mass of 42 kDa), a protein involved in rapamycin signaling through phosphatase regulation (33,34). We cloned the MGC3794 ORF (hereafter referred to as hTIP41) into the TAP tag vectors and repeated the pull-down/identification process with this fusion protein.…”
Section: ; See Below)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as with PP4C, PP4R2 appeared to be present in a complex with PP4R3␣ and/or PP4R3␤. In addition to these proteins, the PP4R2 pull-down also yielded MGC3794, the human homolog of S. cerevisiae Tip41 (Tap42-interacting protein, molecular mass of 42 kDa), a protein involved in rapamycin signaling through phosphatase regulation (33,34). We cloned the MGC3794 ORF (hereafter referred to as hTIP41) into the TAP tag vectors and repeated the pull-down/identification process with this fusion protein.…”
Section: ; See Below)mentioning
confidence: 99%
“…This observation is intriguing because the yeast Tip41 protein was reported to interact with the yeast alpha4 homolog Tap42 and to prevent Tap42 from forming complexes with phosphatases (Ref. 33; see "Discussion"). Finally a pull-down of PP4R3␣ (KIAA2010) confirmed the interaction with PP4C and PP4R2.…”
Section: ; See Below)mentioning
confidence: 99%
“…Moreover, studies in Saccharomyces cerevisiae are contributing significantly to our understanding of the Tor signal transduction pathway in eukaryotic cells. These studies have identified many of the downstream targets of Tor1/2 control as well as participants in the yeast signal transduction pathway itself, including peptidylprolyl isomerase/rotomase, Frp1 (5,6), protein kinase Tap42 (7)(8)(9)(10)(11)(12)(13)(14)46), Tip41 (11,15), type 2A protein phosphatases, Pph21/22 (8,14), Sit4 (7, 8, 14, 16 -18), Pph3 (16), Sit4-associated proteins or SAPS (11,17,19,20), Lst8, which participates in protein trafficking (21)(22)(23), and proteins found in complexes with Tor1/2, Kog1, Avo1-3, Tco89, and Bit6 (21,22).…”
mentioning
confidence: 99%
“…The prevailing model posits that active Tor1/2 phosphorylate Tap42 and Tip41 which, in a way not fully understood, results in inactivation of Sit4, one of two phosphoprotein phosphatases suggested to be responsible for Gln3 dephosphorylation (10,13,17,18). Tor1/2 are also suggested by some investigators to be the kinases responsible for Gln3 phosphorylation itself (13,16).…”
mentioning
confidence: 99%